2013
DOI: 10.5114/wo.2013.34376
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of twenty cases of heterotopic gastric mucosa of upper esophagus during five-year observation, using gastroscopy in combination with histopathological and microbiological analysis of biopsies

Abstract: Aim of the studyHeterotopic gastric mucosa of the upper esophagus (HGMUE) may be connected with disorders of the upper gastrointestinal tract, exacerbated by Helicobacter pylori. Furthermore, HGMUE may be the origin of malignant progression to cervical esophageal carcinoma.Material and methodsIn this work, 20 patients with diagnosed heterotopic gastric mucosa of the upper esophagus (HGMUE) were subjected to 5-year follow-up to determine the extent and structure of histopathological changes within HGMUEs, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Fortunately, a five-year follow up of 20 patients with both cervical heterotopic gastric mucosa and H. pylori infection by Latos et al[36] did not find any malignant transformation, dysplasia or metaplasia. However, their study was potentially limited by a small patient population.…”
Section: Ips and Non-neoplastic Synchronous Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, a five-year follow up of 20 patients with both cervical heterotopic gastric mucosa and H. pylori infection by Latos et al[36] did not find any malignant transformation, dysplasia or metaplasia. However, their study was potentially limited by a small patient population.…”
Section: Ips and Non-neoplastic Synchronous Lesionsmentioning
confidence: 99%
“…In a small case series, the detection of an IP web or ring suggested the pathogenesis of an acid-induced lesion[38]. Importantly, colonization with H. pylori may exacerbate these complications[31,36].…”
Section: Ips and Non-neoplastic Synchronous Lesionsmentioning
confidence: 99%
“…Galan et al 16 were the first investigators who demonstrated acid production of HGMUE islets without any stimuli, by 24‐h pH monitoring. The present study also confirmed that about 70% HGMUE samples showed oxyntic‐ or fundic‐type gland or mixed type, and more than 90% of them were positive staining of H + ‐K + ‐ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…The heterotopic, but otherwise not malignant, epithelium may advance to invasive carcinoma following a metaplasia-dysplasia-carcinoma sequence [ 21 ]. Although the numbers of dysplasia and metaplasia in the diagnosed HGM of the upper oesophagus were limited (about 9% and 12%, respectively), and these lesions were relatively stable clinically, at the present stage of the study we cannot exclude the possibility of malignant progression of HGM into adenocarcinoma of the upper oesophagus [ 22 ].…”
Section: Discussionmentioning
confidence: 99%